2019
DOI: 10.3390/nano9101483
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Tensile Stress Effects on the Structure and Stability of Prototypical Covalent and Layered Materials

Abstract: Understanding the stability limit of crystalline materials under variable tensile stress conditions is of capital interest for technological applications. In this study, we present results from first-principles density functional theory calculations that quantitatively account for the response of selected covalent and layered materials to general stress conditions. In particular, we have evaluated the ideal strength along the main crystallographic directions of 3C and 2H polytypes of SiC, hexagonal ABA stackin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…It has been shown that the one-dimensional (1D) spinodal equation of state can reproduce stress dependence on the strain energy of a given system. The equation of state can be written as …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the one-dimensional (1D) spinodal equation of state can reproduce stress dependence on the strain energy of a given system. The equation of state can be written as …”
Section: Methodsmentioning
confidence: 99%
“…The calculated strain−energy curve is used to obtain the force vs strain curve, which can be used in the spinodal equation of state 45 to determine the critical force and critical strain of a given complex. It is worth mentioning that the spinodal equation of state, in general, applies to the bulk material, but its use has been extended to low-dimensional materials, including graphene and the BN monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the stress-strain curves were obtained by gradually deforming the modelled cell in the direction of the applied displacement and simultaneously relaxing both the atomic basis vectors orthogonal to the applied displacement. As the SiC/Al structure is an atomic configuration in the DFT calculation, the stress value of each graph represents the average stress of the atoms [38,39].…”
Section: Investigation Of Tensile Test Simulation Behaviormentioning
confidence: 99%
“…To determine the mechanical response of the bilayers under the pull-out experimental conditions, we employ the 1D spinodal equation of state [32] which is given by:…”
Section: L ( )mentioning
confidence: 99%